Green container architecture 3 - Garrido, Luis de (Sant Adrià de Besòs, Barcelona Monsa, 2015)
The book aims to demonstrate a methodology to achieve a green and cheap architecture using containers. The containers have been designed to store and transport goods over long distances, and in a tight, economical and safe way. However, it also happens, the curious coincidence that the spaces that have been designed for storing and transporting goods, have a proper human scale. That is, they are also valid for designing living spaces. However containers have not been designed to de lived in. Therefore, the first thing to be done when using containers in architecture is to ensure the minimum conditions of habitability inside. Something that is not taken into account by almost all the proposals. On the other hand, buildings by no means are "green" simply because they have been designed using containers. What's more, most buildings made by containers offer poorer quality of life, and consume more energy than conventional buildings. Therefor, Luis De Garrido analyzes all actions to be carried out in order to make habitable the buildings made by containers, and slo to achieve real sustainable architecture using them. T illustrate these concepts, four advanced container projects designed by Luis De Garrido are analyzed in depth. The book has a strong educational and training value, but at the same time it is a professional and effective tool for all architects and builders, who wish to deal with the sustainable design of buildings made by containers.
L. de Garrido (1967-), Spanish architect.
Keywords: Containers -- Remodelling for other use; Sustainable architecture